Efficacy of Phonophoresis with Chitosan Nanoparticles on Outcome of Patients with Carpal Tunnel Syndrome: A Randomized Controlled Trial - ElGendy, Mohamed H.; Meligie, Mohamed M. El; Zoheiry, Ibrahim M.; Fahmy, Ebtesam M. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to evaluate efficacy of phonophoresis combined with chitosan nanoparticles on patients with mild to moderate carpal tunnel syndrome (CTS). single blind randomized controlled trial . Fifty four hands in 48 consecutive patients with mild to moderate carpal tunnel syndrome were allocated randomly into two groups. Group A (control group, n=27) received a custom made neutral volar splint, therapeutic ultrasound in addition to nerve and tendon gliding exercises. Group B (experimental group, n=27) received the same treatment program with the therapeutic ultrasound applied in the form of phonophoresis combined with chitosan nanoparticles (using ultrasound 1.0 W/cm2 at a 1MHz frequency, pulsed 25% for 5 minutes). All treatment sessions were held 3 d/wk, for 5 weeks. Measurements were performed for pre and post treatment comparison, it included pain assessment by numerical pain rating scale, grip strength by hand held dynamometer, median nerve motor and sensory distal latencies by using electromyography. Statistical analysis using unpaired t-test showed statistically significant improvement in both groups regarding motor distal latency (p< 0.05), sensory distal latency (p< 0.05), pain level (p< 0.05), and hand grip strength (p< 0.05). However, there was a statistically significant improvement in group (B) than group (A) for median nerve motor distal latency, sensory distal latency, pain level and hand grip strength at post treatment. the results of this study showed that adding phonophoresis with chitosan nanoparticles to splinting and exercise therapy was more effective than using splinting and exercise therapy alone for treatment of mild to moderate CTS.